Investigating library staff responses towards reference sevice via texting / Nurul Amira Taib and Syanta Marlisa Relovia Golot - Taib, Nurul Amira; Relovia Golot, Syanta Marlisa (2013)
Libraries hold responsibility to provide information to its user, its serve many kind of user and try to satisfy their users need, thus libraries usually always find a ways to improve their services to serve patrons better. Reference services via texting in libraries can be useful to improve libraries reference services. The purpose of tliis study is to investigating library staffs responses towards reference service via texting. The study also to determine user's knowledge about these services which may be help the library to increase the user satisfaction of the university library's customer services and it is also one of the method to improve the customer service at PTAR. There are only 26 respondents for this research study. The respondents are librarian and library assistants from PTAR 1, PTAR 2, PTAR 3, PTAR 4, FSPU library, INTEC library, Puncak Perdana library and Puncak Alam library.